A Novel qPCR Method for Simultaneous Detection and Quantification of Viable Pathogenic and Non-pathogenic Vibrio parahaemolyticus (tlh+, tdh+, and ureR+) - Niu, Ben; Hong, Bin; Zhang, Zhaohuan; Mu, Lili; Malakar, Pradeep K.; Liu, Haiquan; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2018)
ABSTRACT A novel viable multiplex real-time PCR (novel qPCR) was developed for the simultaneous detection and quantification of pathogenic and non-pathogenic Vibrio parahaemolyticus (V. parahaemolyticus). In this study, the new primer and probe of ureR was used as a surrogate for detection of trh to circumvent the variant trh strains, and the specificity of all primers and probes were tested by 3 standard strains of V. parahaemolyticus,42 clinical strains, 12 wild strains, 4 strains of vibrio spp, and 4 strains of other bacteria. Then, propidium monoazide (PMA) was applied to inhibit DNA of dead cell, and the results of PMA optimized treatments were 15 µM concentration, 5 min incubation periods, 15 min light exposure periods and 30 RPM rotational speed, which resulted in time and cost savings. In addition, two reaction tubes were innovatively proposed to amplify tlh, tdh and ureR respectively, overcoming the complex logical relation of pathogenic and non-pathogenic V. parahaemolyticus. Furthermore, optimal standard curves with a 7-log dynamic range were generated for simultaneously quantifying viable V. parahaemolyticus, and its amplification efficiencies were 108.68, 105.17 and 115.61 % for tlh+, tdh+ and ureR+ respectively. At last, this new assay has been successfully employed to monitor the V. parahaemolyticus contamination rate of shrimp (Penaeus vannamei) and clam (ruditapes philippinarum) from the retail store of major district in Shanghai. In conclusion, this novel qPCR was a powerful method for detection and quantification of viable pathogenic and non-pathogenic V. parahaemolyticus in natural sample, which could support an effective and rapid tool for the authority to monitor the contamination of viable V. parahaemolyticus.